THE INFLUENCE OF LIFE EXPECTANCY IN THE DETERMINATION OF PENSION FUND INVESTMENTS - Farah Kristiani (INTEGRAL, 2013)
Preparating one’s retirement is important for many people, because an employee will often have no salary anymore after retiring, but his/her daily needs are still remained. It is not easy to calculate or estimate the amount of investment funds that must be saved during the active working years to make up for the lack of funds after one’s retirement. This is still the case, even when the case when he/she will receive a pension from the company where he/she worked. In this research we further examine how the life expectancy plays an important role in calculating the amount of necessary fund investments. The results of these calculations are compared with the results without life expectancy. From this analysis, it can be concluded that the required pension fund investments calculated with the life expectancy is much less than the one without life expectancy. This happens because the required pension fund investments are only estimated by assuming that he/she is still alive.Keywords: present value, annuity, pension, investmentPersiapan memasuki usia pensiun penting untuk dilakukan mengingat seorang karya- wan tidak akan mempunyai pemasukan dari gaji setelah dia pensiun, tapi pengelu- aran untuk kebutuhan hidup sehari-hari masih tetap ada. Kesulitan yang sering muncul adalah menghitung berapa besaran dana investasi yang harus dilakukan pada saat masih aktif bekerja supaya mencukupi kekurangan dana setelah seorang karyawan pensiun meskipun ia telah menerima juga tunjangan pensiun dari pe- rusahaan tempatnya bekerja. Pada penelitian ini ditelaah lebih lanjut bagaimana ekspektasi hidup berperan dalam menghitung besaran dana investasi ini. Hasil per- hitungannya dibandingkan dengan perhitungan biasa yang tidak menerapkan ek- spektasi hidup di dalamnya. Dari hasil analisa, dapat disimpulkan bahwa besaran dana pensiun yang dihitung dengan menerapkan ekspektasi hidup, jauh lebih kecil dibandingkan dengan besaran dana pensiun yang dihitung tanpa ekspektasi hidup, karena antisipasi dana investasi pensiun hanya dilakukan selama orang tersebut diasumsikan masih hidup.Kata Kunci: nilai tunai, anuitas, pensiun, investasi.